Perbandingan Tingkat Pemahaman Pendidikan Agama Islam Peserta Didik Berasal dari SMP dan MTs di SMAN 1 Bangsal - FITRIA QURROTUN A'YUNI; R Ratno; Saifuddin Zuhri (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Islamic Junior High School (SMP) and Junior High School (MTs) have similarities in obtaining Islamic Education material at the education strata. Still, several materials delivered at Islamic Junior High School are more than students in Junior High School. The purpose of this study was to determine the level of understanding of students who came from 1) SMP at Public High School (SMA) 1 Bangsal, 2) MTs at SMA 1 Bangsal, and 3) differences in the level of understanding of Islamic Education students from SMP and MTs at SMA 1 Bangsal. The research method uses descriptive quantitative. The results of the study: the level of understanding of Islamic Education students 1) came from SMP at most, namely 31 (38.8%), 2) from MTs at most were good, namely 18 (22.5%), and there were 8 students (10% ) at the excellent level, 3) based on the t-test conclusion, there are differences in the level of understanding of Islamic Education students from SMP and MTs at SMA 1 Bangsal.